Comparing focus groups and individual interviews: findings from a randomized study - Guest, Greg; Namey, Emily; Taylor, Jamilah; Eley, Natalie; McKenna, Kevin (International journal of social research methodology, 2017)
Qualitative researchers often have to decide whether to collect data using focus groups or individual interviews. We systematically compare these two methods on their ability to generate two types of information: unique items in a brainstorming task and personally sensitive disclosures. Our study sample consisted of 350 African-American men living in Durham, North Carolina. Participants were randomized into either a focus group arm or individual interview arm, and were asked the same open-ended questions about their health-care seeking behavior. For the item-generating task, we compared data at two levels of analysis - the event and the individual. At the event level, focus groups and individual interviews generated similar numbers of unique items in a free-listing task. When compared on a per-person basis, however, individual interviews were more effective at generating a broad range of items. We also compared the number of data collection events in which personal, sensitive information was disclosed. We found that several types of sensitive and personal disclosures were more likely in a focus group setting, and that some sensitive themes only occurred in the focus group context. No sensitive themes emerged exclusively, or more often in, an individual interview context. Researchers may use these findings to help align their choice of qualitative data collection method with research objectives.